Faktor Penentu Keputusan Konsumen dalam Mengkonsumsi Teh Celup Sariwangi (Studi Kasus pada Konsumen Tiara Dewata Group di Kota Denpasar) - YUNITA, EVA; SUDARMA, I MADE; DEWI, IDA AYU LISTIA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.6, No.4, Oktober 2017, 2017)
Determinants of Consumer Decisions in Consuming Sariwangi Dye Tea (Case Study on Tiara Dewata Consumer Group in Denpasar City) The consumers’ decision in purchasing Sariwangi tea bag products is affected by consumer characteristics and marketing mix elements. These variables affect the buying decision processes so as to produce a buying decision. This research was conducted at supermarkets in Denpasar City with the aim to identify the factors that play a role in consumer decision to buy Sariwangi tea bags and analyze decision processes of purchasing Sariwangi tea bags by consumers in Denpasar City. In this research, the method used was descriptive-quantitative analysis method and qualitative-descriptive analysis. The results showed that all variables had a role to the consumer's decision to consume Sariwangi tea, the variable that had the greatest role to the secondary factor was the social variable with the communality value of 17.29%, while the individual variable with the communality value of 10.49% had the lowest role to the consumer's decision to consume Sariwangi tea bags. Considering that the seven variables truly have a role to consumer decisions consuming Sariwangi tea, then the producer should still pay attention to matters relating to these variables, especially social factors that have the most decisive role.